There's a boy in the girls bathroom - Sachar, Louis, 1954- (New York : Scholastic, 1987)
An unmanageable, but lovable, eleven-year-old misfit learns to believe in himself when he gets to know the new school counselor, who is a sort of misfit too.
F
490
F
Keywords: Behavior -- Fiction; Friendship -- Fiction; Schools -- Fiction; Counselors -- Fiction